Association between mobile phone use and self-reported well-being in children: a questionnaire-based cross-sectional study in Chongqing, China. Issue 5 (11th May 2015) - Zheng, Feizhou; Gao, Peng; He, Mindi; Li, Min; Tan, Jin; Chen, Daiwei; Zhou, Zhou; Yu, Zhengping; Zhang, Lei
Abstract : Objectives: In the past decade, the mobile phone (MP) has become extremely popular among children and the average age at which children own their first MP has decreased. The potential health effects of children's exposure to MP have been the subject of widespread public concern. The aim of our study is to investigate the associations between MP use and well-being in children. Design: Cross-sectional study. Setting: The questionnaires were completed in class with items regarding demographics, MP usage, self-reported well-being (symptoms were taken from the questionnaire of the HBSC survey) and possible confounding factors between October 2011 and May 2012 in Chongqing, China. Data were analysed using χ 2 tests and logistic regression models. Participants: Among the 793 children invited to participate, 781 returned the questionnaires. Results: In total, 746 (94.1%) valid questionnaires were received. Fatigue was significantly associated with the years of MP usage (OR 1.85; 95% CI 1.07 to 3.22) and the daily duration of MP calls (OR 2.98; 95% CI 1.46 to 6.12). Headache was significantly associated with the daily duration of MP calls (OR 2.85; 95% CI 1.23 to 6.57). However, after adjusting for confounders only, the association between fatigue and MP usage remained statistically significant. There was no significant association between MP use and other physical symptoms in children. Conclusions: The present study indicated that there was a consistent significant association between MP use and fatigue in children. Further in-depth research is needed to explore the potential health effects of MP use in children.